2016
DOI: 10.1186/s12879-016-1663-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cryotherapy for the treatment of cutaneous leishmaniasis: meta-analyses of clinical trials

Abstract: BackgroundCryotherapy is a local treatment for cutaneous leishmaniasis with variable efficacy and greater safety than conventional treatment. The objective of this study is to evaluate the efficacy and safety of cryotherapy for the treatment of cutaneous leishmaniasis and to compare it with pentavalent antimonials.MethodsA meta-analysis based on a search of nine databases with eight strategies was conducted. Inclusion and exclusion criteria were applied, the methodological quality of each article was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 24 publications
2
35
0
2
Order By: Relevance
“…Nevertheless, due to their adverse effects such as myalgia, arthralgia, renal failure, leukopenia, anemia, thrombocytopenia, and cardiotoxicity [23,24] , other local alternatives have been implemented. Currently, cryotherapy is increasingly used for the treatment of cutaneous leishmaniasis, demonstrating a similar efficacy with the pentavalent antimony [25] . Another kind of treatment is currently available involving the application of heat, thermotherapy, demonstrating a greater safety and lower cost, especially in the case of contraindications to systemic treatment [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, due to their adverse effects such as myalgia, arthralgia, renal failure, leukopenia, anemia, thrombocytopenia, and cardiotoxicity [23,24] , other local alternatives have been implemented. Currently, cryotherapy is increasingly used for the treatment of cutaneous leishmaniasis, demonstrating a similar efficacy with the pentavalent antimony [25] . Another kind of treatment is currently available involving the application of heat, thermotherapy, demonstrating a greater safety and lower cost, especially in the case of contraindications to systemic treatment [26] .…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized clinical trial, Farajzadeh found that cryotherapy in combination with oral terbinafine was less effective then cryotherapy with systemic Meglumine Antimoniate. In a meta-analysis, per lesion efficacy of 67.3% and 67.7% were reported for cryotherapy and pentavalent antimonials respectively [15]. In a case series for multiple recurrent Actinic keratosis sequential treatment of diclofenac 3% gel with cryotherapy was found to be an effective treatment [16].…”
Section: Discussionmentioning
confidence: 99%
“…Both therapies are used in Mexico and in some regions worldwide [22]. Antibacterials as penicillin or antifungal creams (such as miconazole, ketoconazole, or itraconazole) are applied on the lesion [40]. Mexican patients have also used acetic acid, boric acid, sulfuric acid (car battery acid), formalin, alcohol, hydrogen peroxide, wire and copper sulfate, among other remedies [22,42].…”
Section: Extract and Pure Compounds Obtained From Mexican Medicinal Pmentioning
confidence: 99%